Causal association of inflammatory bowel disease with sarcoidosis and the mediating role of primary biliary cholangitis - Yick, Chich (Frontiers in Immunology, 2024)
Objectives: Previous observational epidemiological studies have identified a potential association between Inflammatory bowel disease (IBD) and sarcoidosis. Nonetheless, the precise biological mechanisms underlying this association remain unclear.Therefore, we adopted a Mendelian Randomization (MR) approach to investigate the causal relationship between IBD with genetic susceptibility to sarcoidosis, as well as to explore the potential mediating role.The genetic associations were obtained from publicly available genomewide association studies (GWAS) of European ancestry. Dataset of IBD with 31,665 cases and 33,977 controls, consisting of 13,768 Ulcerative colitis (UC) and 17,897 Crohn's disease (CD). The genetic associations of sarcoidosis with 2,046 cases and 215,712 controls. A bidirectional causality between IBD and sarcoidosis was implemented to determine by two-sample MR approach. The inverse variance weighted (IVW) method was utilized as the main statistic method, and a series of sensitivity analyses were performed to detect heterogeneity and horizontal pleiotropy. Using a two-step MR approach to investigate whether the mediating pathway from IBD to sarcoidosis was mediated by PBC.The forward MR analysis indicated that genetically predisposition to IBD was significantly linked to an increased risk of sarcoidosis (OR=1.088, 95%CI:1.023-1.158, PIBD-sar=7.498e-03). Similar casual associations were observed in CD (OR=1.082, 95%CI:1.028-1.138, PCD-sar=2.397e-03) and UC (OR=1.079, 95%CI:1.006-1.158, PUC-sar=0.034). Reverse MR analysis revealed that genetic susceptibility to sarcoidosis was correlated with an augmented risk of CD (OR=1.306, 95%CI:1.110-1.537, Psar-CD=1.290e-03) but not IBD or UC. The mediation analysis via two-step MR showed that the causal influence of IBD and CD on sarcoidosis effects was partly mediated by PBC, the mediating effect was 0.018 (95%CI:0.005-0.031, P=7.596e-03) with a mediated proportion of 21.397% in IBD, and 0.014 (95%CI:0.004-0.024, P=7.800e-03) with a mediated proportion of 17.737% in CD.The MR analysis provided evidence substantiating the causal effect of IBD (CD and UC) on an increased risk of sarcoidosis, with PBC playing a mediating role in IBD and CD. However, sarcoidosis only enhances the risk of developing CD, but not IBD or UC.These findings illuminate the etiology of sarcoidosis and contribute to the management of IBD patients.